THE IMPACT OF ARTIFICIAL INTELLIGENCE TECHNOLOGY ON INTERNATIONAL TRADE - Qian Zuo Yin; Lai Wei Sieng, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This paper studies the complex impact mechanism of AI (artificial intelligence) technology on international trade. This provides an answer to how different countries use AI technology to increase their own international trade volume. This article is based on an analysis of cross-sectional data for 139 countries in 2021. This paper uses the Ordinary Least Square (OLS) method to perform a analysis on the cross-sectional data. This paper finds that the membership of World Trade Organization (WTO) has obvious significance for a country to use AI technology to promote exports. In countries with a high Government AI Readiness Index, AI technology has a significant role in promoting the growth of international trade. However, there is a significant negative correlation between the number of patent applications for AI-related technologies and imports and exports across countries. Besides, the number of patent applications for AI-related technologies has a direct heterogeneous impact on the imports of countries with different income groups. AI technology is an emerging technology. To study the impact of this technology on international trade, multiple factors of AI technology must be considered at the same time. For countries that are not members of the WTO, joining the WTO can make better use of AI technology to promote the development of their international trade. Between the complex relationship between the number of patent applications for different AI-related technologies and international trade, countries with different income groups should develop AI technologies that are beneficial to their own international trade.